Sport Tourism Dan Event-Induced Hotel Demand: Studi Kasus Jakarta Running Festival Pada Hotel Artotel Gelora Senayan - Maya Maysyarofah; Agus Sholikhin; Alip Suroto (Bata Ilyas Educational Management Review, 2026)
Abstrak Penyelenggaraan event olahraga berskala besar berpotensi meningkatkan permintaan akomodasi dan memengaruhi operasional hotel. Penelitian ini bertujuan menganalisis dampak Jakarta Running Festival terhadap permintaan kamar, strategi operasional Hotel Artotel Gelora Senayan, serta pengalaman tamu selama periode event. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus melalui wawancara, observasi, dan studi dokumentasi. Data dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa Jakarta Running Festival meningkatkan permintaan kamar karena lokasi hotel yang dekat dengan kawasan Gelora Bung Karno. Hotel merespons melalui strategi revenue management, koordinasi lintas departemen, penyesuaian staf, serta peningkatan kualitas layanan. Temuan ini menunjukkan bahwa dampak event tidak hanya meningkatkan okupansi, tetapi juga mendorong penyesuaian strategi operasional dan pengalaman tamu. Kata kunci: sport tourism; event-induced hotel demand; Jakarta Running Festival; tingkat hunian hotel; pengalaman tamu. Abstract Large-scale sporting events can increase accommodation demand and influence hotel operations. This study aims to analyze the impact of the Jakarta Running Festival on room demand, operational strategies, and guest experiences at Artotel Gelora Senayan Hotel. A qualitative single-case study approach was employed using in-depth interviews, non-participant observations, and document analysis. The data were analyzed through thematic analysis. The findings show that the Jakarta Running Festival increased room demand due to the hotel's strategic location near the Gelora Bung Karno sports complex. In response, the hotel implemented revenue management strategies, strengthened cross-departmental coordination, adjusted staffing levels, and enhanced service quality. These findings indicate that sporting events not only increase hotel occupancy but also encourage operational adjustments and improve the overall guest experience. Keywords: sport tourism; event-induced hotel demand; Jakarta Running Festival; hotel occupancy; guest experience.